2021
DOI: 10.1002/app.51910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene oxide functionalized by phytic acid for anticorrosive reinforcement of waterborne epoxy coating

Abstract: Graphene derivatives are excellent fillers for providing outstanding barrier performance in organic protective coating but no active inhibition property. In this paper, a facile and environmentally friendly strategy is presented to improve the anticorrosion ability of graphene by modifying graphene oxide (GO) with a green corrosion inhibitor derived from nature, phytic acid (PA). The as-prepared PA modified GO (PAGO) thus possesses the passive barrier property and active corrosion inhibition function simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In particular, the anticorrosive performances of graphene oxide intercalated phytic acid are well-known in the literature [ 79 , 80 , 81 , 82 ]. Moreover, the sol–gel process is widely employed for the preparation of thin films, thanks to their chemical inertness, outstanding resistance, and mechanical properties [ 83 , 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the anticorrosive performances of graphene oxide intercalated phytic acid are well-known in the literature [ 79 , 80 , 81 , 82 ]. Moreover, the sol–gel process is widely employed for the preparation of thin films, thanks to their chemical inertness, outstanding resistance, and mechanical properties [ 83 , 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are many hydrophilic groups or segments on the WEP backbone or side chains which can accelerate the penetration of corrosive medium. 8,9 It has been demonstrated that the introduction of nanofillers (such as graphene oxide, 10 hexagonal boron nitride, 11 polyaniline (PANI), 12 etc.) can fill the pores during the WEP coating curing process, and thus effectively alleviate the penetration of corrosive medium, enhancing the anticorrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the introduction of nanofillers (such as graphene oxide, hexagonal boron nitride, polyaniline (PANI), etc.) can fill the pores during the WEP coating curing process, and thus effectively alleviate the penetration of corrosive medium, enhancing the anticorrosion properties. Wang et al prepared N-doped carbon quantum dots (N-CQDs)-modified graphene (N-CQDs@Gr), stably dispersing in water over 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The excellent anticorrosion properties of graphene coatings have been proved by many researchers. [24][25][26] However, the black color of graphene prevents its application in UV-cured coating. Mica is a silicate mineral with acid and alkali resistance, chemical inertness, excellent electrical insulation, and temperature stability, which has been widely used as filler.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its unique platelet structure and high aspect ratio, two‐dimensional inorganic fillers, such as graphene, 18 mica, 19 glass flake, 20 and boron nitride, 21 have attracted great interests as anticorrosion fillers, which could form a multilayered labyrinth structure to extend the diffusion pathway to aggressive medium and enhance the barrier property of the coating 22,23 . The excellent anticorrosion properties of graphene coatings have been proved by many researchers 24–26 . However, the black color of graphene prevents its application in UV‐cured coating.…”
Section: Introductionmentioning
confidence: 99%